The impact of the diode laser 940 nm photoactivated bleaching on color change of different composite resin restorations - Amal Alaa Mawlood; Niaz H Hamasaeed (Wolters Kluwer Medknow Publications, 2023)
The study's main objective was to evaluate as well as compare the impact of diode laser 940 nm and conventional in-office bleaching technique on the color change of different composite resin restorations. A total of ninety composite resin discs (CRDs) were made from Filtek™ Bulk Fill, nanohybrid composite resin Filtek™ Z550 XT Universal Restorative, and flowable composite resin restoration Filtek™ Z350xt Flowable Composite. Group A: (30) CRD for Filtek™ Bulk Fill, group B: (30) CRD for Filtek™ Z550 XT Universal Restorative, and group C: (30) CRD for Filtek™ Z350xt Flowable Composite. A1, B1, and C1: (10 CRD in each group): Control group without bleaching. A2, B2, and C2: 10 CRD in each group bleached with Laser White20 without laser activation. A3, B3, and C3: 10 CRD in each group bleached with Laser White20 and activated by diode laser 940 nm. The color was evaluated using a dental spectrophotometer. One-way ANOVA was utilized for the comparison of the color stability of the CRD. P < 0.05 is regarded as statically significant. Both conventional and diode laser in-office vital tooth bleaching protocols affected the color stability of composite resin restorations. The result demonstrated that bleaching without laser activation produced color change (mean [8.30], standard deviation [SD] (1.95) P [< 0.001]), whereas the bleaching and activation by diode laser produced color change (mean [8.11], SD [1.99], P [< 0.001]). Both types of bleaching protocol affected composite resin restorations' color stability. In all tested materials, color changes after the bleaching protocol were clinically perceptible. The restorations following the bleaching procedure are required to be replaced by clinicians.